SCHIZOPHRENIC OBSTRUCTION TO SUCCESS IN JOE WRIGHT'S THE SOLOIST MOVIE (2009): A PSYCHOANALYTIC PERSPECTIVE - ASTININGSIH, EKA SURYANTY (2011)
This study is about how is schizophrenic can obstruct the success of the major character in The Soloist movie. The objective of the study is to analyze the film based on its structural analysis and based on the psychoanalytic analysis. This study is descriptive qualitative research that the data are taken from script of The Soloist movie by using methodology of literature as the references. The object of the study is The Soloist movie directed by Joe Wright and based on the book written by Steve Lopez. The data sources are divided into two namely primary data source and secondary data source. The primary data source is the film itself and the secondary data source is the other sources relating to the analysis such as references, author's biography, criticisms relating to the problems and material relating to the study whether picking up from books, articles or internet. The result of the study shows as follows. First, based on structural analysis the writer has successfully delivered the message through all structural elements. Each of the structural elements relates to one another forming a unified whole. Second based on the psychoanalytic analysis, the problems of the major character cause the conflict of his mental condition. It happens when there is contradiction between id, ego, and superego and it brings him into schizophrenia.